2020
DOI: 10.1177/0017896920981122
|View full text |Cite
|
Sign up to set email alerts
|

Layla’s Got You: Developing a tailored contraception chatbot for Black and Hispanic young women

Abstract: Introduction: In Onondaga County, New York, around half of all births to Black and Hispanic teenage girls are unintended. The Layla’s Got You campaign consists of a chatbot and social media campaign designed to increase contraception knowledge among 16- to 25-year-old Black and Hispanic women in Onondaga County. Methods: The campaign was co-created with local women in the target audience and employed digital and grassroots community building strategies. Focus groups were conducted among 31 women, during which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…One study that stands out is the work of Bonnevie and colleagues [ 16 ], who describe the development of Layla , a trusted source of information in contraception and sexual health among a population at higher risk of unintended pregnancy. Layla was designed and developed through community-based participatory research, where the community that would benefit from the chatbot also had a say in its design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study that stands out is the work of Bonnevie and colleagues [ 16 ], who describe the development of Layla , a trusted source of information in contraception and sexual health among a population at higher risk of unintended pregnancy. Layla was designed and developed through community-based participatory research, where the community that would benefit from the chatbot also had a say in its design.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, there is no obvious correlation between application domains, chatbot purpose, and mode of communication (see Multimedia Appendix 2 [ 6 , 8 , 9 , 16 - 18 , 20 - 45 ]). Some studies did indicate that the use of natural language was not a necessity for a positive conversational user experience, especially for symptom-checking agents that are deployed to automate form filling [ 8 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a tool for providing tailored messaging, social listening, and 2-way dialogue, automated conversational agents, or chatbots, were cited early in the pandemic as a promising tool to offer COVID-19 health guidance on demand [ 19 , 20 ]. Chatbots have provided support on a range of health issues including chronic disease, addiction, reproductive health, depression, and anxiety, with promising adaptations of evidence-based interventions such as cognitive behavioral therapy [ 21 - 25 ]. This approach may appeal especially to young adults, since a substantial proportion of millennials, born from 1981-1996, are more trusting of web-based information and better equipped to use health technology than earlier generations [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated how visual, conversational, and identity-related cues trigger “humanness heuristics” ( 18 , 19 ) and affective states in users similar to natural human communication ( 20 ). Design factors such as physical appearance ( 21 ), gender ( 22 , 23 ), and speech dialect ( 24 ) can be tailored to match users' cultural and demographic background and help to establish rapport ( 15 , 20 ) and perceptions of a CA's personality ( 25 ). Language-based cues are of particular importance due to their strong role in driving user engagement ( 1 ).…”
Section: Introductionmentioning
confidence: 99%